(untitled) (Pedagogy of Higher and Secondary Education, 2004)
The article shows the essence of the students’ playing activity during their foreign language communication training. The author gives the examples o f using some kinds of games in practice and demonstrates the effectiveness of using playing activities of students as prospective teachers in order to prepare them to foreign communication.